Physiological traits associated with increasing grain number in wheat (Triticum aestivum L.) and their genetic regulation - Garner, James (2022)
Previous studies suggest that genetic variation in grain yield potential in wheat is associated with grain sink strength under favourable conditions, which is mainly determined by grain number. Even in suboptimal conditions, increasing grain sink strength raises yield potential and attainable yield in wheat. Therefore, the elucidation of novel grain number traits such as fruiting efficiency (FE, ratio of grain number to spike dry weight at anthesis) and grain dry matter partitioning in wheat is crucial for genetic gains and food security. However, the physiological and genetic basis of these traits is not fully understood. The objectives of this study were, using a winter wheat KWS panel, to identify novel grain number and partitioning traits for increased harvest index and grain yield, and to determine marker-trait associations and candidate genes through a genome wide association study. The association panel of 138 KWS winter wheat genotypes was phenotyped for grain number and partitioning traits in field experiments at anthesis and physiological maturity in two seasons near Cambridge, UK. A subset of eight genotypes representative of field variation for FE was grown in the glasshouse under well-watered conditions at the University of Nottingham, UK in two years for analysis of flag-leaf gas exchange traits and their association with grain number traits and grain yield. To examine if specific plant organs and stem internodes were competing with the spike at anthesis, samples were taken in the field and glasshouse where the plants were separated into their component parts (ear, stem (including stem internodes), leaf sheath and leaf lamina.